George W. Dean (1820-1901), Amateur Malacologist in Ohio - Ralph W. Dexter (Hello World!, 1969)
George W. Dean was born in Wayne Town ship of Ashtabula County, Ohio, on 20 August 1820. He was educated in the common schools of that township and at the Western Reserve Academy at Farmington. As a young man he followed in his father's footsteps as a shoe-maker in Wayne Township and later at Auburn. On 1 September 1852 he was married to Maria L. Jones. They had one daughter, Lillian, born in 1853, who shared her father's interest in horticulture and natural history.